Chronic patellofemoral instability and pain treated effectively by anteromedial tibial tubercle transfer (Fulkerson osteotomy) with or without medial patellofemoral ligament reconstruction - Mukhopadhaya, John; Gupta, Arvind; Sinha, Amit K.; Bhadani, Janki S. (International Journal of Research in Orthopaedics, 2021)
Background-Chronic patellar instability (subluxation and dislocation) and pain is a debilitating knee condition that frequently involves young, active patients. Bony malalignment and soft tissue injury (torn or stretched MPFL) is considered as a surgical indication for distal realignment in the form of Anteromedial tibial tubercle transfer(Fulkerson osteotomy) with or without MPFL reconstruction that effectively prevents the patella from tracking laterally and thus unloads the lateral patella while making the patellofemoral joint more congruous , stable and pain free. Materials and method - It is a prospective study of 22 patients of chronic patellar instability and pain. Follow up ranged from 24 to 36(average 30) months. Preoperative assessment included clinical examination, Lysholm, IKDC score and Radiological examination (X-ray, CT scan and MRI). 18 patients with history of dislocation and pain having bony malalignment and torn MPFL were treated with Fulkerson osteotomy and MPFL reconstruction and 4 patients with history of subluxation and pain having bony malalignment only were treated with Fulkerson osteotomy alone. Patients were followed up with the help of X-rays at regular interval and the clinical outcome was measured using scoring system. Results-There was a significant improvement in postoperative assessment with regards to scoring system (Lysholm and IKDC) and knee pain. Union at osteotomy site for all patients was seen. None of the patients had further episode of dislocation or subluxation. Pain at femoral site of MPFL reconstruction in 2 cases persisted for 3 months followed by resolution of their symptoms. One of our patients had profuse swelling at the site of operation postoperatively which was treated with Rest, Ice Pack, Compression and Limb elevation. Out of 22 patients undertaken infection at osteotomy site was seen in 1 patient for which implant removal was done from osteotomy site after union. Conclusion-Anteromedial Tibial tuberosity osteotomy and MPFL reconstruction is a successful procedure to treat patellofemoral pain and instability.